Secretion of urokinase and plasminogen activator inhibitor-1 by normal colonic epithelium in vitro. Issue 7 (July 1994) - Gibson, P; Rosella, O; Rosella, G; Young, G
Abstract : Urokinase is a neutral protease whose major site of action is the external surface of the plasma membrane of cells and whose major function seems to be modulation of cell adhesion, such as that which occurs during cell migration. This study aimed to determine whether colonic epithelium is involved with the urokinase system. The contents of urokinase and one of its specific inhibitors, plasminogen activator inhibitor-1, were measured in culture supernatant and cell homogenates of isolated human colonic crypt cells. The amounts of both factors increased in supernatants over 24 hours, and approximately twice the amount was found in supernatants than in autologous cell homogenates. The secretion of both factors was similar in serum free and serum containing media. Northern blot analysis showed that messenger ribonucleic acid specific for urokinase and plasminogen activator inhibitor-1 was present in colonic crypt cells and that expression over 18 hours of culture was increased 12 fold for urokinase type plasminogen activator and two to fourfold for the inhibitor compared with values found in autologous freshly isolated cells. Urokinase activity was detected in crypt cell homogenates and supernatants indicating that it was present in excess of its inhibitors. Control experiments indicated that the epithelial cells themselves were responsible for the observations and excluded artefactual effects of the isolation procedure. In conclusion, isolated human colonic epithelial cells secrete urokinase and at least one of its specific inhibitors. Further investigation of the role of urokinase in the physiology and pathophysiology of colonic epithelium is indicated.